Rod-Shaped Magnetite Nano/Microparticles Synthesis at Ambient Temperature - Balaprasad Ankamwar; Ashwini Thorat (Journal of Chemistry)
Here, we reported room temperature synthesis of Fe3O4 rod-shaped nano/microparticles by chemical reduction method from FeCl3 precursor and NaBH4 as the reducing agent in the presence of the pyrrole as a capping agent. The magnetic Fe3O4 particles were characterized by several methods, such as SEM, XRD, FTIR, and TGA. The average aspect ratio of Fe3O4 rod-shaped particles was ~2.8. These particles were redispersed in deionised water to form a colloidal solution and showed magnetic properties. This economical synthesis route is scalable, and Fe3O4 particles can be exploited for various applications such as MRI contrast enhancement, biodiseperations, Ni-Fe batteries, and as a catalyst.